2020
DOI: 10.11606/s1518-8787.2020054003278
|View full text |Cite
|
Sign up to set email alerts
|

Population-based seroprevalence of SARS-CoV-2 and the herd immunity threshold in Maranhão

Abstract: OBJECTIVE: To estimate the seroprevalence of SARS-CoV-2 in the state of Maranhão, Brazil. METHODS: A population-based household survey was performed, from July 27, 2020 to August 8, 2020. The estimates considered clustering, stratification and non-response. Qualitative detection of IgM and IgG antibodies was performed in a fully-automated Elecsys® Anti-SARS-CoV-2 electrochemiluminescence immunoassay on the Cobas® e601 analyzer (Roche Diagnostics). RESULTS: In total, 3,156 individuals were interviewed. Seroprev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
4
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
(49 reference statements)
5
15
4
6
Order By: Relevance
“…This suggests the actual number of SARS-CoV-2 infections in Nicaragua was higher than official reports, which might be explained by a high rate of asymptomatic and mild cases that did not seek medical attention, or by limited testing of patients who received medical attention. Our seroprevalence results are similar to those of another study from Brazil, 7 and those reported from SARS-CoV-2 hot spots in high income countries, such as Massachusetts and Northern Italy, although the Massachusetts study was not carried out in a population-based cohort. 2,8 In these studies, the seroprevalence of SARS-CoV-2 antibodies was higher than expected based on the reported incidence of symptomatic SARS-CoV-2 infections in the area.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests the actual number of SARS-CoV-2 infections in Nicaragua was higher than official reports, which might be explained by a high rate of asymptomatic and mild cases that did not seek medical attention, or by limited testing of patients who received medical attention. Our seroprevalence results are similar to those of another study from Brazil, 7 and those reported from SARS-CoV-2 hot spots in high income countries, such as Massachusetts and Northern Italy, although the Massachusetts study was not carried out in a population-based cohort. 2,8 In these studies, the seroprevalence of SARS-CoV-2 antibodies was higher than expected based on the reported incidence of symptomatic SARS-CoV-2 infections in the area.…”
Section: Discussionsupporting
confidence: 90%
“…We identified high seroprevalence among younger age groups, particularly in children between 5 and 14 years of age (42%). Age-based differences in seropositivity were observed in Brazil and Italy, 2,7 however, they were more pronounced in our population. High seropositivity in children might be due to continued operation of public schools throughout the epidemic.…”
Section: Discussioncontrasting
confidence: 66%
“…Para o cálculo do tamanho da amostra, adotou-se a prevalência de infectados por SARS-Cov-2 estimada no primeiro inquérito realizado no estado do Maranhão 16 . Em cada estrato, o cálculo do tamanho da amostral foi estimado a partir da seguinte equação: A seleção dos domicílios em cada um dos 150 setores ou agrupamentos foi obtida por amostra sistemática.…”
Section: Amostraunclassified
“…Os sintomas também foram investigados por meio da recordação, segundo o mês em que estiveram presentes. Porém, para averiguar a frequência dos sintomas, foram usados os mais associados ao diagnóstico da covid-19, anosmia/hiposmia ou ageusia/disgeusia 16 . Sobre a intenção de tomar a vacina, a pergunta foi feita quando a vacinação ainda não estava ocorrendo, com poucos detalhes divulgados sobre como seria executada.…”
Section: Variáveis Em Estudounclassified
See 1 more Smart Citation